SYNTHESIS OF LINEAR Α-OLEFIN (LAO) FROM ETHYLENE GAS USING CR(III) PHENOXY-IMINE AND NI(0) PHOSPINE - EKO SETIO WIBOWO (NIM: 10512017),
Linear α-olefin (LAO) such as 1-hexene is used as comonomers for the production of branched polyethylene, such as linear low density polyethylene (LLDPE). One method of 1-hexene synthesis is trimerization of ethylene gas. Catalysts are used in this reactions commonly require a cocatalyst as an activator in large numbers. For example, the chromium(III) PNP catalyst from BP Chemical requires methylaluminoxane (MAO) as cocatalyst with 300 mol equivalent. The titanium(IV) phenoxy-imine catalyst from Mitsui Chemical, requires MAO 10,000 mol equivalent. Thus the development of catalyst innovation without the activator in large quantities is required. In this study, the author proposes the catalyst design of chromium(III) phenoxy-imine that is predicted to pass through the stages of ethylene trimerization via the formation of metallacycle intermediate. The chromium(III) phenoxy-imine catalyst is activated through the reduction process of chromium(III) to chromium(I) that accompanied by chloride ligands release. This phase also aims to provide vacant sites on the chromium complex that serves as the active catalyst. The catalytic activity test was carried out by reacting ethylene gas as much as 8 bars, zinc powder and tetrahydrofuran solvent at a temperature of 65 oC for 24 hours. Based on the gas chromatographic analysis results, the expected LAO product has not been formed. As an alternative, synthesis of LAO from ethylene is done through different stages of the reaction by using a nickel(0) phosphine catalyst. The results of GC analysis showed the presence of a new peak between 1-hexene and 1-octene standards, which is predicted belong to 1-heptene.